Garmin Running Dynamics Pod ni veljaven za določanje kontaktnih časov pri teku na mestu - Drobnič, Miha (Šport (Ljubljana), 2023)
Garmin Running Dynamics Pod is a sensor that gives a user an insight into several parameters of running dynamics. The accuracy of the data obtained is crucial for the successful monitoring of progress in various sports. The aim of the research was to check the validity of the mentioned device in the determination of contact times, so we compared the obtained data with the data from the bilateral force plate (gold standard). Subjects (n = 11; age = 23 ± 3 years; body weight = 74 ± 17 kg and body height = 176 ± 10 cm) performed three 20-second bouts of running in place of varying intensity, all self-chosen. They started with a slow, followed by medium and finished with a fast intensity. The results showed statistically significant differences in all four conditions (slow, medium, fast, and total frequency; p <0.001) with the lowest bias at high frequency (-81.5 ± 18.4 ms). The Garmin Running Dynamics Pod is designed to calculate running parameters in normal conditions, but it has proved invalid compared to the gold standard for determining running in place contact times.
Keywords: Garmin Running Dynamics Pod; kontaktni čas; senzorji teka; šport; tek; tek na mestu